Increased interleukin-9 and Th9 cells in patients with refractory Graves’ disease and interleukin-9 polymorphisms are associated with autoimmune thyroid diseases - Yao, Qiuming; Song, Zhenyu; Wang, Bin; Du, Peng; Qin, Qiu; Zhao, Jing; Zhang, Jin-an (Frontiers in Immunology, 2024)
Autoimmune thyroid diseases (AITDs) are prevalent disorders, primarily encompassing Graves' disease (GD) and Hashimoto's thyroiditis (HT). Despite their common occurrence, the etiology of AITDs remains elusive. Th9 cells, a new subset of CD4 + T cells with immunomodulatory properties, have been linked to the development of various autoimmune diseases. However, research on the role of Th9 cells in AITDs is limited. We investigated the expression of Th9 cells, their functional cytokine IL-9, and transcription factor IRF4 in peripheral blood mononuclear cells (PBMCs) and plasma of AITD patients and healthy controls. Additionally, we explored the genetic association between four loci polymorphisms (rs31564, rs2069879, rs1859430, and rs2069868) of the IL-9 gene and AITDs. We reported, for the first time, that refractory GD patients exhibited elevated mRNA levels of IL-9 and IRF4 in PBMCs, increased IL-9 protein levels in plasma, and a higher proportion of Th9 cells in peripheral blood when compared to normal controls. Furthermore, human recombinant IL-9 protein was found to enhance IFN-γ secretion in PBMCs from both GD patients and normal controls.At the genetic association level, after adjusting for age and sex, the rs2069879 polymorphism exhibited a significant association with AITDs under an additive model (P<0.001, OR= 0.05, 95% CI=0.03-0.08) . Our results reveal that Th9 cells may exert a pivotal role in the pathogenesis and progression of refractory GD and HT, and IL-9 holds promise as a novel therapeutic target for the management of AITDs.